Improvement of Engineering Characteristics of Poor Quality Soil by mixing with Bottom Ash - Wipula, W.K.; Priyankara, N.H. (University of Jaffna, 2022)
Huge quantity of bottom ash is generated as a by-product of burning of coal when generating electricity at Norochcholai power plant. However, only very small quantity of bottom ash is used by the industry to produce concrete blocks and remaining is stockpiled at Norochcholai creating an environmental pollution. As such, possibility to utilize bottom ash for road embankment and pavement construction was studied in this research study. Different percentages of bottom ash were mixed with poor quality soils, which were not satisfied the filling material requirements in the specification, to improve the engineering characteristic of soils. Based on the results, it can be noted that by blending 30% of bottom ash with poor quality soil, it can be used as an embankment Type 1 and Type 2 filling material. Further, it was found that by adding 10% of cement to soil-bentonite mixture, it can be utilized as a subbase material. Hence, it can be concluded that bottom ash can be used successfully as a mechanically stabilizer to improve the engineering characteristics of poor quality soil.
Keywords: Bottom ash; CBR value; Cement; Poor quality soil